2021
DOI: 10.1038/s41598-021-03190-2
|View full text |Cite
|
Sign up to set email alerts
|

The deleterious effects induced by an acute exposure of human skin to common air pollutants are prevented by extracts of Deschampsia antarctica

Abstract: The homeostatic and regenerative potential of the skin is critically impaired by an increasing accumulation of air pollutants in human ecosystems. These toxic compounds are frequently implicated in pathological processes such as premature cutaneous ageing, altered pigmentation and cancer. In this scenario, innovative strategies are required to tackle the effects of severe air pollution on skin function. Here we have used a Human Skin Organotypic Culture (HSOC) model to characterize the deleterious effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…RelB gene was shown to mediate another non-canonical pathway by interaction with AhR and binding to an unrecognized genomic RelB/AhR responsive element (RelBAhRE) ( Vogel et al, 2007 ). As a result, production of inflammatory markers was shown to stimulate melanin production ( Khmaladze et al, 2020 ; Fernández-Martos et al, 2021 ; Nkengne et al, 2021 ; Moon et al, 2022 - detailed in Table 1 ), another cross talking point in the complex pathways network governing melanogenesis (see Section 3.6 ).…”
Section: Intracellular Signaling Pathways Crosstalk: Impacts Of Air P...mentioning
confidence: 99%
See 2 more Smart Citations
“…RelB gene was shown to mediate another non-canonical pathway by interaction with AhR and binding to an unrecognized genomic RelB/AhR responsive element (RelBAhRE) ( Vogel et al, 2007 ). As a result, production of inflammatory markers was shown to stimulate melanin production ( Khmaladze et al, 2020 ; Fernández-Martos et al, 2021 ; Nkengne et al, 2021 ; Moon et al, 2022 - detailed in Table 1 ), another cross talking point in the complex pathways network governing melanogenesis (see Section 3.6 ).…”
Section: Intracellular Signaling Pathways Crosstalk: Impacts Of Air P...mentioning
confidence: 99%
“…Natural extracts from plants such as Deschampsia Antarctica ( Milani et al, 2019 ; Fernández-Martos et al, 2021 ) and Korean Red Ginseng ( Moon et al, 2022 ) were evaluated for anti-pollution claims. In a clinical study, Deschampsi Antarctica reduced dark spots ( Milani et al, 2019 ); the study by Fernández-Martos et al, 2021 supported mechanistically the claims on this natural extract and identified the AhR and inflammatory pathways as those on which the extract is effective. Furthermore, the same study used an ex vivo human skin model that was pre-treated with Deschampsia Antarctica and then exposed to different pollutants.…”
Section: Testing Platforms Used To Study Pigmentation In the Context ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a plant capable of surviving in hostile environmental conditions, such as high radiation, high salinity, high oxygen concentration, low temperature, and extreme dryness, due to protection mechanisms against environmental aggression. Edafence® has been shown to reduce the effects of various pollutants on the skin and it strengthens the skin's barrier function, thus improving overall pigment control efficacy [31,32], as clinical studies have shown that environmental pollution can worsen pigmentation disorders such as melasma [33].…”
Section: Journal Of Clinical and Cosmetic Dermatologymentioning
confidence: 99%
“…Thus, for instance, it has been shown (Pereira et al 2009;Gidekel et al 2014;Perez-Davó et al 2019;Zamarrón et al 2019) that the compounds extracted from D. antarctica plants demonstrate antioxidant activity and may be used as photoprotective and antiaging agents. D. antarctica plant extract was found to protect human skin fibroblasts from the action of aggressive oxidants and environmental pollutants (Ortiz-Espіn et al 2017;Fernández-Martos et al 2021). The biological activity of extracts is associated, in particular, with the availability of substances with antioxidant properties, e.g., polyphenols.…”
Section: Introductionmentioning
confidence: 99%

Polish Polar Research

Ivannikov,
Anishchenko,
Kuzema
et al. 2022